2022
DOI: 10.1097/brs.0000000000004448
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Transcranial Stimulated Motor-Evoked Potential Alerts in Cervical Spine Surgery Varies Based on Preoperative Motor Status

Abstract: Study Design. A prospective multicenter observational study. Objective. The aim was to investigate the validity of transcranial motor-evoked potentials (Tc-MEP) in cervical spine surgery and identify factors associated with positive predictive value when Tc-MEP alerts are occurred. Summary of Background Data. The sensitivity and specificity of Tc-MEP for detecting motor paralysis are high; however, false-positives sometimes occur. Materials and Methods. The authors examined Tc-MEP in 2476 cases of cervic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
2
2
Order By: Relevance
“…22,23 Kobayashi et al reported that multimodal IONM is essential during high-risk spinal surgery, such as adult spinal deformity, spinal cord tumor, and OPLL. 24,25 In this study, the positive predictive value of cases with traumatic spinal surgery, cervical, and thoracic injury surgeries were 17.9%, 19.0%, and 25.0%, respectively, which were relatively lower than previous reports related to high-risk spinal surgeries. We understand that using TcMEP for non-high-risk spinal surgery with lower paralysis rates yields a lower positive predictive value as compared with that for high-risk spinal surgery.…”
Section: Effect Of Tcmep Monitoring During Traumatic Spinal Injury Su...contrasting
confidence: 66%
See 3 more Smart Citations
“…22,23 Kobayashi et al reported that multimodal IONM is essential during high-risk spinal surgery, such as adult spinal deformity, spinal cord tumor, and OPLL. 24,25 In this study, the positive predictive value of cases with traumatic spinal surgery, cervical, and thoracic injury surgeries were 17.9%, 19.0%, and 25.0%, respectively, which were relatively lower than previous reports related to high-risk spinal surgeries. We understand that using TcMEP for non-high-risk spinal surgery with lower paralysis rates yields a lower positive predictive value as compared with that for high-risk spinal surgery.…”
Section: Effect Of Tcmep Monitoring During Traumatic Spinal Injury Su...contrasting
confidence: 66%
“…Patients with greater spinal cord compression and those who undergo surgery at thoracic levels are prone to severe spinal cord compromise and are at high risk of intraoperative neurological complications 22,23 . Kobayashi et al reported that multimodal IONM is essential during high-risk spinal surgery, such as adult spinal deformity, spinal cord tumor, and OPLL 24,25 . In this study, the positive predictive value of cases with traumatic spinal surgery, cervical, and thoracic injury surgeries were 17.9%, 19.0%, and 25.0%, respectively, which were relatively lower than previous reports related to high-risk spinal surgeries.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Some conditions, such as herniated discs, may respond well to conservative treatments such as physical therapy or chiropractic care, while other conditions such as spinal tumors or fractures may require surgery. Funaba et al (2022) examined the individual techniques, their anatomical and physiological bases, and their use in spinal surgery as trustworthy indications of functional injury, their limitations, and their usage to particular surgically surgical procedures, such as the lateral transposes access for antibody fusion and the divergent trajectory for cortico-pedicular screws. To assess the effect of IONM departure disposal, medical expenditures, and hospital-based obstacles, a multivariate analysis with modifications for patient a factor was utilized (George et al (2019)).…”
Section: Introductionmentioning
confidence: 99%